Preparation and characterization of Schiff base nickel complexes and their application in the coupling reaction of cyclohexene oxide and carbon dioxide. Issue 8 (18th July 2022) - Hsu, Shih‐Hsien; Chen, Hung‐Chih; Hung, Yu‐Ching; Li, Yi‐Xuan; Liu, Guan‐Lin; Ko, Bao‐Tsan; Lin, Chu‐Chieh
Abstract: A series of novel nickel complex (1 –10 ) supported by NNO‐tridentate Schiff‐base ligands (L 1 H–L 10 H) were synthesized and used as catalysts for the reaction of cyclohexene oxide (CHO) and carbon dioxide. Structure determination reveals that all of these complexes are di‐nuclear species with either hexa‐coordinated Ni centers [(OAc)Ni(μ‐L)2 (μ‐H2 O)Ni(OAc)] (1 –6, 9 –10 ) or penta‐coordinated Ni centers [(LNi(μ‐OAc)2 NiL] (7 –8 ) with respect to various electronic and steric effect. Interestingly, experimental results indicated that these complexes were inactive in the reaction of CO2 and CHO in the absence of co‐catalysts. However, they exhibited efficient activity and high selectivity yielding cyclic carbonate in the presence of ammonium halides. Among them, complexes with more steric bulky ligand showed somewhat higher activity. Kinetic studies reveal the reaction of CHO and CO2 catalyzed by 4 in the presence of 4 equiv of n Bu4 NCl as co‐catalyst yielding cyclic carbonate with active energy (ΔG ‡ ) of 59.1 kJ/mol, ΔH ‡ of 55.86 kJ/mol and ΔS ‡ of −118.28 J/(mol × K) indicating association of substrates occurs prior to the rate‐determining step. Abstract : A series of NNO‐Schiff base‐supported nickel complexes were prepared and used as catalysts for the coupling reaction of CO2 /CHO yielding cyclic carbonate as the sole product.